KEPADATAN (MAN BITING RATE) NYAMUK ANOPHELES DI DESA RANOKETANG TUA, KECAMATAN AMURANG KABUPATEN MINAHASA SELATAN - Joy V.I Sambuaga; Risman S. Duka; Djani Hermanus (POLTEKKES KEMENKES MANADO, 2019)
Malaria is the most important tropical parasitic disease in the world, and is still a major health problem. South Minahasa Regency was ranked 4th in Malaria Morbidity Rate (API) in 2017. Ranoketang Tua Village was one of the highest cases of malaria, 61 cases, based on data from the 2017 health center. This study aimed to determine the diversity and density (Man Biting Rate) of Mosquitoes Anopheles in Ranoketang Tua Village, Amurang District, South Minahasa Regency. This research is a type of descriptive research. The samples in this study were Anopheles mosquitoes that were caught through the method of insider bait (UOD) and outsider bait (UOL) identified by the species and calculated the Man Bitting Rate (the number of Mosquitoes Biting per person per night). Research Results Found three species of Anopheles namely An. barbirostis, An. tesselatus and An. flavirostris. Density of Anopheles sp mosquitoes in Ranoketang Tua Village, namely An Mosquitoes. barbirostris MBR 49, An Mosquito. flavirostris MBR 3.75 and An Mosquito. tesselatus MBR 0.125. Suggestions to the public to use insecticide-treated mosquito nets, use mosquito coils or reppelant during sleep and wear long-sleeved clothing when doing outdoor activities at night. In order to avoid mosquito bites and reduce the population of Anopheles sp.